Ответ:
Пошаговое объяснение:
1) -3.2*0.4+2.6*(-0.5) = -1.28 + (-1.3) = -2.58.
2) 4 7/12 * (-1 3/11) - (-1 1/15) * (-45/64) = -6 7/12.
1. 4 7/12 * (-1 3/11) = -(4*12+7)/12 * (1*11+3)/11 = -55/12 * 14/11 = -35/6 = -5 5/6;
2. (-1 1/15) * (-45/64) = 16/15 * 45/64 = 3/4;
3. -5 5/6 - 3/4 = -(5 10/12 + 9/12) = -5 19/12 = -6 7/12.
3) -6 2/5 * 1 9/16 + (-2 1/4)^2 = -32/5*25/16 + (-9/4)^2 =
= -10 + 5,0625 = −4,9375.
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Ответ:
Пошаговое объяснение:
1) -3.2*0.4+2.6*(-0.5) = -1.28 + (-1.3) = -2.58.
2) 4 7/12 * (-1 3/11) - (-1 1/15) * (-45/64) = -6 7/12.
1. 4 7/12 * (-1 3/11) = -(4*12+7)/12 * (1*11+3)/11 = -55/12 * 14/11 = -35/6 = -5 5/6;
2. (-1 1/15) * (-45/64) = 16/15 * 45/64 = 3/4;
3. -5 5/6 - 3/4 = -(5 10/12 + 9/12) = -5 19/12 = -6 7/12.
3) -6 2/5 * 1 9/16 + (-2 1/4)^2 = -32/5*25/16 + (-9/4)^2 =
= -10 + 5,0625 = −4,9375.